The effectiveness of digital health intervention on glycemic control and physical activity in patients with type 2 diabetes: a systematic review and meta-analysis - Xue, Haoyuan; Zhang, Lin; Shi, Yarong; Zhang, Hao; Zhang, Chuanrong; Liu, Yang; Tan, Wenshu; Liu, Yaorong (Frontiers in Digital Health, 2025)
IntroductionDigital health interventions (DHIs) offer promising strategies for managing type 2 diabetes mellitus (T2DM), yet their efficacy on physical activity remains inconsistent. This systematic review and meta-analysis evaluates DHIs' effectiveness across key clinical endpoints.MethodsFollowing PRISMA guidelines and PROSPERO registration (CRD420251032375), five databases (Web of Science, Embase, Scopus, Cochrane, PubMed) were searched through February 2025. Randomized controlled trials (RCTs) assessing DHIs (mobile applications, phone calls or SMS, online platforms, remote monitoring) versus usual care in T2DM patients were included. Primary outcomes were HbA1c, fasting blood glucose (FBG), postprandial blood glucose (PBG), HOMA-IR, and physical activity. Risk of bias was evaluated using Cochrane RoB 2. Meta-analyses employed random/fixed-effect models in Review Manager 5.3, with subgroup and sensitivity analyses for heterogeneity (I² > 50%).ResultsFrom 9,499 records, 118 RCTs (21,662 participants) were analyzed. DHIs significantly reduced HbA1c (MD = −0.32% to −0.54%), FBG (MD = −0.30 to −0.85), and PBG (SMD = −0.58) versus controls (p < 0.05). Subgroup analyses indicated online platforms most effectively lowered HbA1c (MD = −0.54). No improvements occurred in HOMA-IR (MD = −0.18, 95% CI: −0.79 to 0.44) or physical activity (SMD = 0.16, 95% CI: −0.08 to 0.39). Cost analyses revealed lower expenses in DHI groups (mean: 269.31 vs. 465.37). High heterogeneity (I² = 69–92%) was observed for glycemic outcomes, partially explained by intervention duration and sample size in meta-regression.DiscussionDHIs demonstrate robust efficacy for glycemic management in T2DM, particularly through online platforms and remote monitoring. However, they fail to enhance physical activity or insulin resistance. Future studies should prioritize adaptive designs for sustained behavioral change and investigate long-term cost-effectiveness.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251032375, identifier (CRD420251032375).